Perilaku Ibu Rumah Tangga dalam Menggunakan Kelambu sebagai Upaya Pencegahan Malaria di Wilayah kerja Puskesmas Kabukarudi Kabupaten Sumba Barat Tahun 2014 - Anderias Tarawatu Ora; Bagoes Widjanarko; Ari Udijono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTThe kelambunisasi program is one of the efforts undertaken in West Sumba Regency to prevent and cope with malaria. However, data from the West Sumba District health office shows that the incidence of malaria in the work area of the Puskesmas Kabukarudi continues to increase. In 2011 the API value was 32.380 / 00. Next in 2012 the API value increases to 64,000 / 00. This study aims to determine the factors - factors that influence the behavior of the use of mosquito nets in housewives. The type of this research is explanatory research with cross sectional approach. The number of samples in this study were 130 housewives. Data analysis was done univariat, bivariate with Chi-Square, and multivariate with logistic regression. The results showed that most respondents (54.70%) used mosquito nets well. The most dominant variable affecting the behavior of using mosquito net is perception of family head support. Variables related to the behavior of mosquito net use were perception variable about malaria disease and use of mosquito net, attitudes toward the use of mosquito net, perception of family head support in using mosquito net, and exposure of information about malaria disease and use of mosquito net.Keywords: Housewives, behavioral use of mosquito nets, prevention of malaria